MODERASI WORD OF MOUTH DALAM MENENTUKAN KEPUTUSAN PEMBELIAN PADA D’KRIUK FRIED CHICKEN DI KELURAHAN KILENSARI SITUBONDO - Pratanca, Gusti Pandu; Fandiyanto, Randika; Ediyanto, Ediyanto (Fakultas Ekonomi dan Bisnis, 2025)
The fast food industry in Indonesia continues to grow rapidly, along with the increasing public need for practical and affordable food. Lifestyle changes that tend to be fast-paced make fast food the leading choice for many people. Competition in this sector is getting tougher from global brands and local players who continue to innovate. Today’s consumers are looking for practicality and a pleasant consumption experience. Companies in this sector need to be able to adapt to evolving trends and preferences. One of the growing local brands is D’Kriuk Fried Chicken, which is located in various regions, including Kilensari Village and Situbondo. This research analyzes and tests brand image, product diversity, and service quality in purchasing decisions through customer satisfaction as a moderating variable at D’Kriuk Fried Chicken in Kilensari Village, Situbondo. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study using the Smart PLS 3.0 application. The results of the direct effect hypothesis test showed that Brand image weakens the relationship positively to purchasing decisions, product diversity strengthens the relationship significantly positively to purchasing decisions, service quality strengthens the relationship significantly positively to purchasing decisions, word of mouth weakens the relationship positively to the role of Brand image in improving purchasing decisions.